Should We All Give up Meat To Save the Environment? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Before deciding to cut meat from our diets as a way to reduce green house gas emissions, we should consider the other effect of removing livestock from the environment. Interview with Phil Thornton (CCAFS/ILRI) and Andy Jarvis (CIAT). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya